2011
DOI: 10.1111/j.1365-2095.2009.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary copper requirement of juvenile yellow catfish Pelteobagrus fulvidraco

Abstract: The present experiment was conducted to quantify dietary copper (Cu) requirement for juvenile yellow catfish Pelteobagrus fulvidraco. The six experimental diets were formulated to contain the graded levels of CuSO4·5H2O (0, 0.005, 0.01, 0.02, 0.04 and 0.08 g kg−1 diet respectively) providing the actual dietary copper values of 2.14 (control), 3.24, 4.57, 7.06, 12.22 and 22.25 mg Cu kg−1 diet respectively. Each diet was fed to triplicate groups of yellow catfish (initial body weight: 3.13 ± 0.09 g, means ± SD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
67
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 27 publications
18
67
0
2
Order By: Relevance
“…In the present study, fish were fed the Cu deficient diet produced a slower growth rate than the adequate Cu diet, in agreement with several reports (Ogino and Yang, 1980;Lin et al, 2008;Tan et al, 2011), indicating that Cu content in the rearing water could not meet the requirements of fish and therefore dietary supplementation was necessary. However, dietary Cu excess also resulted in growth retardation, in agreement with other reports (Kim and Kang, 2004;Shaw and Handy, 2006;Lin et al, 2008;Tan et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, fish were fed the Cu deficient diet produced a slower growth rate than the adequate Cu diet, in agreement with several reports (Ogino and Yang, 1980;Lin et al, 2008;Tan et al, 2011), indicating that Cu content in the rearing water could not meet the requirements of fish and therefore dietary supplementation was necessary. However, dietary Cu excess also resulted in growth retardation, in agreement with other reports (Kim and Kang, 2004;Shaw and Handy, 2006;Lin et al, 2008;Tan et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…At present, optimal dietary Cu requirement has been determined in many fish species, ranging from 3 to 10 mg Cu kg − 1 feed, which depends on the species, feeding regime and life stage (Clearwater et al, 2002;NRC, 2011). Studies have also shown that over-loading of dietary Cu in fish caused toxic syndrome (Handy, 1996;Berntssen et al, 1999a;Lundebye et al, 1999;Shiau and Ning, 2003), including reduced growth (Clearwater et al, 2002;Shaw and Handy, 2006;Tan et al, 2011), severe lesions in the gut (Handy, 1996), and subtle changes in intestinal cell proliferation and turnover (Berntssen et al, 1999a;Lundebye et al, 1999). In contrast, dietary Cu deficiency has been shown to reduce appetite, growth and cause anemia in several fish (Ogino and Yang, 1980;Gatlin and Wilson, 1986;Shiau and Ning, 2003;Lin et al, 2008;Tan et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…At present, different parameters have been used to determine mineral requirement in fish, including growth performance (Lin et al, 2010;Pan et al, 2008;Tan et al, 2011), feed utilization (Luo et al, 2010, tissue mineral concentration (Lin et al, 2008;Luo et al, 2010;Maage et al, 2000;Pan et al, 2008;Tan et al, 2011) and hepatic Mn-SOD activity (Lin et al, 2008). Our present study indicated that Mn requirements obtained from WG, PER and hepatic Mn-SOD activities were similar, whose values were 5.5, 5.6 and 6.4 mg kg − 1 diet, respectively.…”
Section: Discussionsupporting
confidence: 57%